Variability and Character Association Study in Morphological Traits of Tossa Jute (Corchorus olitorius L.) (The Agriculturists, 2020)
Tossa jute (CorchorusolitoriusL.) is the most important commercial crop of Bangladesh. Fifty-six genotypes of F2 generation were raised at Breeding Research Farm, Hajee Mohammad Danesh Science and Technology University, Dinajpur from April 2018 to August 2019 from the parental lines O-9897, O-795, JRO-524, Acc. 2381, Acc. 3423, Acc. 3438, Acc. 3533 and Acc. 3860. The parameters, plant height (m), base diameter (mm), green bark thickness (mm), green bark weight without leaves (g), stick weight (g), fiber strength (MPa), days to flowering, days to maturity and fiber weight/stick varied significantly among the genotypes. Significant productivity was found from Acc. 3860. Green bark weight without leaves exhibited highest genotypic and phenotypic co-efficient of variation followed by fiber weight and stick weight. The highest genetic advance as percentage of mean (44.38%) was estimated against green bark weight without leaves suggest it as a prime character that enhanced fiber and stick yields. The Acc. 3860 resulted high production of fiber in hybrids. Considering the studied characters, the F2-generation of Acc. 3860 is comparatively batter than others. The research findings suggested that the F2-generation of Accession Acc. 3860 may produce desired segregates and therefore demands farther research in different environmental conditions and field trail.The Agriculturists 2020; 18(1) 116-128